The Influence of Internal Control System, Follow-Up on Audit Recommendations, and Government Accounting Standards Implementation on Audit Opinion with Regional Loss as Mediator - Moh Faris Nur Wahib; Abdul Rohman (Media Ekonomi dan Manajemen, 2025)
This study analyses the influence of the effectiveness of the Internal Control System (ICS), follow-up on audit recommendations, and the implementation of Government Accounting Standards (GAS) on local government audit opinions, with regional losses as a mediating variable. The study is motivated by a contradictory phenomenon. While the quality of audit opinions has generally improved, regional losses have significantly increased over the past six years, peaking at IDR 2,457,241.66 million in 2023. The research utilises secondary data from the Audit Board of Indonesia (BPK), covering 1,012 observations from city and regency governments during 2022–2023. The data analysis using Partial Least Squares Structural Equation Modeling (SEM-PLS).The study finds that (1) ICS effectiveness significantly affects regional losses but not audit opinions, (2) follow-up on audit recommendations has no significant effect on either audit opinions or regional losses, (3) GAS implementation significantly affects both audit opinions and regional losses, and (4) regional losses do not mediate the relationships between the independent variables and audit opinion. These findings highlight the theoretical relevance of Agency Theory and provide practical and policy implications for improving local government financial accountability and audit outcomes.